The breathing wall - Pullinger, Kate 1961-; Schemat, Stefan; Babel ([Kate Pullinger with Stefan Schemat and babel], 2004)
"The Breathing Wall is a digital fiction that responds to the reader's rate of breathing. The innovative software enables the computer to register the physiological effect of the story on the reader and to alter the experience accordingly. The more relaxed the reader becomes, the deeper they enter into the piece. The Breathing Wall tells the story of a girl, Lana, communicating with her boyfriend, Michael, through the wall of his prison cell. She is dead; he's been falsely convicted of her murder. The story is told in parts, alternating between day-dreams and night-dreams. The day-dreams use image, text and sound to uncover the tale through a linear multimedia narrative. The night-dreams use video and sound loops; to experience the night-dreams the reader needs a headset that includes earphones and a microphone. By positioning the microphone under your nose, the night-dreams respond to your breathing. The goal of these sections is to induce a hypnotic or meditative state in the reader, allowing he or she to enter the dream."--Katepullinger.com